THE ANALYSIS OF THE RESULTS OF ACUTE LYMPHOBLAST LEUKEMIA TREATMENT IN CHILDREN USING A MODIFIED PROTOCOL COALL 92 IN ST. PETERSBURG - E.G. Boichenko; M.B. Ivanovskaya; I.A. Garbuzova; M.A. Shul’gina; M.S. Livshits; T.N. Kulakova; T.A. Makarova; M.B. Belogurova; G.G. Radulesku; T.D. Viktorovich; E.D. Chavpetsova; M.M. Sokolova; et al. (Педиатрическая фармакология, 2006)
The article presents the results of the treatment of children with acute lymphoblast leukemia (all) according to the coall 92 program in St.-Petersburg from 01.01.1999 to 01.01.2005. 160 primary all patients, aged 4 months to 17 years 4 months were included in the study. International criteria were used to diagnose acute lymphoblast leukemia. A 2 years course of treatment in both risk groups included a 5,5–8 months phase of intensive chemotherapy followed by maintenance therapy. 6 years after the protocol introduction in the common group of patients the following survival rate indices were obtained: the 6 years uneventful survival rate was 63 ± 4,6%, the 6 years relapses free survival rate was 69 ± 4,7%, the 6 years general survival rate was 79 ± 3,7%.Key words: acute lymphoblast leukemia, children, intensive chemotherapy.